Sexually transmissible infections among transgender men and women attending Australian sexual health clinics. Issue 9 (29th August 2019) - Callander, Denton; Cook, Teddy; Read, Phillip; Hellard, Margaret E; Fairley, Christopher K; Kaldor, John M; Vlahakis, Emanuel; Pollack, Alisa; Bourne, Christopher; Russell, Darren B; Guy, Rebecca J; Donovan, Basil
Abstract: Objectives: To estimate rates of HIV infection, chlamydia, gonorrhoea, and infectious syphilis in transgender men and women in Australia; to compare these rates with those for cisgender people. Design: Cross‐sectional, comparative analysis of de‐identified health data. Setting, participants: We analysed data for 1260 transgender people (404 men, 492 women, 364 unrecorded gender), 78 108 cisgender gay and bisexual men, and 309 740 cisgender heterosexual people who attended 46 sexual health clinics across Australia during 2010–2017. Main outcome measures: First‐visit test positivity for sexually transmitted infections (STIs), stratified by patient group and year; demographic and behavioural factors associated with having STIs. Results: 14 of 233 transgender men (6.0%) and 34 of 326 transgender women (10%) tested during first clinic visits were chlamydia‐positive; nine transgender men (4%) and 28 transgender women (8.6%) were gonorrhoea‐positive. One of 210 tested transgender men (0.5%) and ten of 324 tested transgender women (3.1%) were diagnosed with infectious syphilis; 14 transgender men (3.5%) and 28 transgender women (5.7%) were HIV‐positive at their first visit. The only significant change in prevalence of an STI among transgender patients during the study period was the increased rate of gonorrhoea among transgender women (from 3.1% to 9.8%). Compared with cisgender gay and bisexual men, transgender men were less likely (adjusted odds ratio [aOR], 0.46; 95% CI, 0.29–0.71; P = 0.001) and transgender women as likely (aOR, 0.98; 95% CI, 0.73–1.32; P = 0.92) to be diagnosed with a bacterial STI; compared with heterosexual patients, transgender men were as likely (aOR, 0.72; 95% CI, 0.46–1.13; P = 0.16) and transgender women more likely (aOR, 1.56; 95% CI, 1.16–2.10; P = 0.003) to receive a first‐visit bacterial STI diagnosis. Conclusions: The epidemiology of STIs in transgender people attending Australian sexual health clinics differs from that of cisgender patients. Gender details must be captured by health data systems to facilitate appropriate delivery of sexual health care.